Early human impacts on vegetation on the northeastern Qinghai-Tibetan Plateau during the middle to late Holocene. (June 2017) - Huang, Xiao-zhong; Liu, Si-si; Dong, Guang-hui; Qiang, Ming-rui; Bai, Zhi-juan; Zhao, Yan; Chen, Fa-hu
The ecosystems of the Qinghai-Tibetan Plateau are regarded as being primarily regulated by climate because of the harsh environment of the region and the resulting sparse human population. Recent studies have revealed that Neolithic farmers and nomads extensively settled in the northeastern Qinghai-Tibetan Plateau from 5.2 ka (ka = cal ka BP); however, it is unclear how and to what extent human activity has affected its vegetation. Here we combine the results of the pollen analysis of a sediment core from Genggahai Lake, a shallow lake in Gonghe Basin on the northeastern Qinghai-Tibetan Plateau, with archaeological evidence and use them to assess the extent and nature of human impacts on the regional vegetation during the middle and late Holocene. The pollen record indicates that Stellera, an indicator of the extent of grazing-induced grassland degradation, first appeared at 4.7 ka, expanded during 3.6–3.0 ka, and finally increased significantly after 1.6 ka. In support of this finding, archaeological data indicate that the agro-pastoral Majiayao people arrived at ∼5 ka and groups of Kayue people, who practiced pastoralism, intensively colonized the Gonghe Basin and nearby Qinghai Lake basin during 3.6–3.0 ka. After ∼1.6 ka, from the Tang Dynasty onwards, human settlement and grazing activity intensified on the northeastern Qinghai-Tibetan Plateau, and this is in accord with the observed high percentages of Stellera in the pollen record. Based on comparison with other records, we conclude that the sediments of Genggahai Lake provide a record of anthropogenic impacts on vegetation, and that human activity may have contributed to regional forest decline during the middle Holocene, and to grassland degradation in the late Holocene. Grassland degradation caused by human activity may be an indicator of the start of the Anthropocene and potentially may have contributed to global climate change via increased dust emission to the atmosphere.